Contribuições do wordwall para inclusão escolar de adolescentes neurodivergentes: um estudo de caso em uma escola da rede municipal de Fortaleza-CE - Lima, Marcos Antonio Rocha de (2024)
This dissertation has as its research object the development of a virtual digital game, aimed at children with Autism Spectrum Disorder 3 ASD. Thus, the general objective was to develop an educational game for neurodivergent children in the final years of elementary school with the help of the WordWall platform. This is a qualitative, descriptive research that adopted design thinking as a data collection technique with the following steps: immersion, ideation, analysis, testing and evaluation. The research subjects were five students with autism spectrum disorders and three teachers from a municipal school in Fortaleza, from August 2023 to March 2024. The data collection instruments were a field diary and semi-structured interview, in addition to observation participant. In the first stage, the planning phase of the didactic sessions, development, testing of the prototype and evaluation by the subjects took place. The results indicate that there was an increase in student motivation, involvement and interest of autistic students. Teachers emphasize that the development of a digital game can contribute to increasing the attention, concentration and logical reasoning of elementary school students diagnosed with ASD, as long as the needs of this target audience regarding adequate usability and who are unaware of the resource are met. The advantages include being free, easy to use and adapt, however it requires improvements such as the inclusion of avatars, texts and videos. It is concluded that Wordwall, as a teaching resource, presents a list of models of interactive or printed activities, available for the teacher to create their own activities according to the content studied and the planned objectives, helping the pedagogical practices of the Physical Education discipline, enabling the teacher, even if he or she does not have knowledge of the programming language, to reach the interest of students, including neurodivergent ones. It is suggested as future work that the research be expanded to other disciplines and other audiences as an alternative to school inclusion.